Electrophotographic belt and method for manufacturing the same, and electrophotographic image forming apparatus
Patent Information
- Application Number
- JP2024125645
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-27
AI Technical Summary
【0009】 本開示の少なくとも一の態様によれば、トナーの離形性と、弾性層と無機粒子の接着性とを高いレベルで両立させることができる電子写真ベルトとその製造方法を得ることができる。また、本開示の少なくとも一の態様によれば、高品位な電子写真画像を安定的に形成することができる電子写真画像形成装置を得ることができる。
Smart Images

Figure 2025027434000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic belt used in an electrophotographic image forming apparatus such as a copying machine or a printer, a method for manufacturing the same, and an electrophotographic image forming apparatus. [Background technology]
[0002] In electrophotographic image forming apparatuses capable of forming color images, a tandem method is widely adopted in which toner images of each color of Y, M, C, and K are superimposed on an intermediate transfer belt, which is an electrophotographic belt, and then transferred all at once onto paper to obtain a full-color image. In such an image forming apparatus, an intermediate transfer belt having at least one elastic layer (hereinafter, also referred to as "elastic intermediate transfer belt") may be used to further improve image quality. Patent Document 1 discloses an intermediate transfer belt having an elastic layer and a release layer made of silicone rubber, which has excellent conformity to the surface shape of a recording medium. In addition, an elastic intermediate transfer belt having an elastic layer as a surface layer may have insufficient toner releasability, and transfer efficiency may decrease. Therefore, Patent Document 2 discloses a coating layer made of a silane coupling agent on an intermediate layer, which may be an elastic layer, in order to improve the toner releasability on the surface of the elastic intermediate transfer belt. Then, a configuration is disclosed in which resin fine particles such as silicone fine particles are embedded in the coating layer and exposed to the surface. In addition, Patent Document 3 discloses a configuration in which fine particles are embedded in the surface of the elastic layer, and an uneven shape is formed on the surface of the elastic layer by the silicone fine particles, thereby improving the toner releasability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-194822 A [Patent Document 2] JP 2015-121585 A [Patent Document 3] JP 2014-215470 A [Patent Document 4] Japanese Patent Application Publication No. 8-187773 Summary of the Invention [Problem to be solved by the invention]
[0004] However, according to the study by the present inventors, in order to prevent the silicone fine particles from falling off in the configuration in which the silicone fine particles are embedded, it is necessary to increase the amount of silicone fine particles embedded in the coating layer or the elastic layer, as disclosed in Patent Documents 2 and 3. As a result, there are cases in which sufficient toner releasability cannot be imparted to the surface of the intermediate transfer belt.
[0005] At least one aspect of the present disclosure is directed to providing an electrophotographic belt capable of achieving both high levels of toner releasability and high levels of adhesion between an elastic layer and inorganic particles, and a manufacturing method thereof. At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Means for solving the problem]
[0006] According to at least one aspect of the present disclosure, An electrophotographic belt comprising a base layer and an elastic layer on the base layer, the elastic layer includes rubber and has a thickness of at least 250 μm; a first surface of the elastic layer opposite to a surface facing the base layer holds a plurality of inorganic particles such that at least a portion of each of the inorganic particles is exposed from the elastic layer, and the elastic layer and the plurality of inorganic particles are in direct contact with each other; Regarding the outer surface of the electrophotographic belt, The electrophotographic belt has a Taber abrasion test performed according to ASTM D1044 using an abrasive wheel CS10F at a rotation speed of 60 rpm and a rotation number of 1000 under conditions of a load of 4.90 N and a rate of the number of inorganic particles in the contact portion with the abrasive wheel after the Taber abrasion test to the number of inorganic particles present in the portion corresponding to the contact portion before the Taber abrasion test of 70% or more.
[0007] According to at least one aspect of the present disclosure, There is provided a method for producing the above electrophotographic belt, comprising the following steps (i) to (iii): (i) a surface treatment step of subjecting the first surface of the elastic layer to a hydrophilic treatment so as to include a hydroxyl group; (ii) a coating step of coating inorganic particles onto the first surface treated in step (i); (iii) a bonding step of bonding the elastic layer and the inorganic particles by a dehydration condensation reaction between the hydroxyl groups on the first surface and the surface functional groups of the inorganic particles.
[0008] According to at least one aspect of the present disclosure, an image forming unit including an image carrier, a charging means, an image exposure means, and a developing means; An electrophotographic image forming apparatus including an intermediate transfer body, a primary transfer member for primarily transferring a toner image formed on the image carrier onto the intermediate transfer body, and a secondary transfer member for secondarily transferring the toner image on the intermediate transfer body to a recording material, There is provided an electrophotographic image forming apparatus in which the intermediate transfer member is the electrophotographic belt described above. Effect of the Invention
[0009] According to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic belt and a manufacturing method thereof that can achieve both high levels of toner releasability and high levels of adhesion between the elastic layer and inorganic particles. Also, according to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic diagram of a cross section of an electrophotographic belt according to one aspect of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view of an image forming apparatus using an electrophotographic belt according to one embodiment of the present disclosure. [Diagram 3] 1A to 1C are explanatory diagrams of a method for fixing inorganic particles to an elastic layer according to the present disclosure. [Figure 4] 11 is an explanatory diagram of a process of adhering silica particles to the surface of an elastic layer in an electrophotographic belt according to Comparative Example 3. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0012] Hereinafter, an electrophotographic belt, a manufacturing method for an electrophotographic belt, and an electrophotographic image forming apparatus according to an embodiment of the present disclosure will be described in detail with reference to the drawings. However, the scope of the present disclosure is not limited to only this embodiment, and modifications that do not depart from the gist of the present disclosure are also included in the present disclosure.
[0013] The electrophotographic belt according to one embodiment of the present disclosure is a laminated body composed of at least a base layer 101, an elastic layer 102, and inorganic particles 103, as shown in FIG. As described later, the inorganic particles 103 are arranged independently in the planar direction on a first surface of the elastic layer 102 opposite the surface facing the base layer, and there is almost no overlap between the particles in the layer thickness direction or complete embedment in the elastic layer 102, forming a substantially single layer.
[0014] (base layer) The base layer 101 in the present disclosure will be described. The base layer 101 in the present disclosure is a seamless cylindrical type in the form of a roll or belt. Examples of materials suitable for the base layer 101 include the following resin materials: polyether ether ketone, polyethylene terephthalate, polybutylene naphthalate, polyester, polyimide, polyamide, polyamideimide, polyacetal, polyphenylene sulfide, etc. The resin for the base layer 101 may be made conductive by adding conductive powder such as metal powder, conductive oxide powder, conductive carbon, etc. In the present disclosure, polyether ether ketone or polyimide with added carbon black is particularly preferred from the viewpoint of obtaining excellent mechanical strength and conductivity. Considering the use as an intermediate transfer body, the film thickness of the base layer 101 is preferably 10 μm or more and 500 μm or less, and more preferably 30 μm or more and 150 μm or less.
[0015] (Elastic layer) An elastic layer 102 is formed on the outer peripheral surface of the base layer 101. By providing the elastic layer 102, the toner on the surface layer of the electrophotographic belt can be made to conform to the surface irregularities of paper or the like, which is a recording material. Examples of materials for the elastic layer 102 include natural rubber, styrene-butadiene rubber, butadiene rubber, isoprene rubber, nitrile rubber, chloroprene rubber, butyl rubber, ethylene-propylene rubber, chlorosulfonated rubber, acrylate rubber, epichlorohydrin rubber, urethane rubber, silicone rubber, fluororubber, etc. Among these, silicone rubber is preferred because of its small compression set and excellent ozone resistance. The hardness of the elastic layer 102 is preferably 15 degrees or more and 80 degrees or less, and more preferably 30 degrees or more and 60 degrees or less, in terms of type A hardness. In addition, the thickness of the elastic layer 102 is at least 250 μm, taking into consideration mechanical strength and flexibility, and is preferably 250 μm or more and 500 μm or less, and more preferably 250 μm or more and 400 μm or less.
[0016] The elastic layer 102 may contain an electronic conductive agent or an ionic conductive agent as a conductive agent. Examples of electronic conductive agents include conductive carbon black such as acetylene black and ketjen black, graphite, graphene, carbon fiber, and carbon nanotubes. Examples of electronic conductive agents include metal powders such as silver, copper, and nickel, conductive zinc oxide, conductive calcium carbonate, conductive titanium oxide, conductive tin oxide, and conductive mica. Of these, conductive carbon black is preferred from the viewpoint of ease of control of electrical resistance. Examples of the ionic conductive agent include ionic liquids of pyridine, alicyclic amine, and aliphatic amine, in addition to lithium salts and potassium salts. Of these, ionic liquids are preferred from the viewpoint of environmental stability and suppression of polarization due to durability. From the viewpoint of mechanical strength, the compounding formulation for the elastic layer 102 is preferably 35 parts by mass or less, more preferably 25 parts by mass or less, per 100 parts by mass of silicone rubber. There is no particular restriction on the lower limit, but it is preferably 0.1 parts by mass or more. This provides the elastic layer 102 with stable conductivity suitable for an electrophotographic belt.
[0017] The elastic layer 102 may also contain additives such as fillers, crosslinking accelerators, crosslinking retarders, crosslinking assistants, scorch inhibitors, antiaging agents, softeners, heat stabilizers, flame retardants, flame retardant assistants, ultraviolet absorbers, and rust inhibitors. In particular, examples of the fillers include reinforcing fillers such as fumed silica, crystalline silica, wet silica, fumed titanium oxide, and cellulose nanofibers. The reinforcing fillers may be surface-modified with an organosilicon compound from the viewpoint of being easily dispersed in silicone rubber. For example, examples of the organosilicon compound include organoalkoxysilanes, organohalosilanes, organosilazanes, diorganosiloxane oligomers in which both ends of the molecular chain are blocked with silanol groups, and cyclic organosiloxanes.
[0018] In order to bond the base layer 101 and the elastic layer 102 more firmly, a primer may be applied to the outer surface of the base layer 101. The primer used here is a paint in which a silane coupling agent, a silicone polymer, hydrogenated methylsiloxane, an alkoxysilane, a reaction-accelerating catalyst, and a colorant such as red iron oxide are appropriately mixed and dispersed in an organic solvent. A commercially available product can be used as the primer. The primer treatment is performed by applying the primer to the outer surface of the base layer 101 and drying or baking it. The primer can be appropriately selected depending on the material of the base layer 101, the type of the elastic layer, or the form of the crosslinking reaction. In particular, when the elastic layer 102 contains a large amount of unsaturated aliphatic groups, a primer containing a hydrosilyl group is preferably used to impart adhesion by reaction with the unsaturated aliphatic groups. An example of a commercially available primer having such characteristics is DY39-051A / B (trade name, manufactured by Dow Corning Toray Co., Ltd.). In addition, when the elastic layer 102 contains a large amount of hydrosilyl groups, a primer containing an unsaturated aliphatic group is preferably used. An example of a commercially available primer having such characteristics is DY39-067 (trade name, manufactured by Toray Dow Corning Co., Ltd.). Examples of primers include those containing alkoxy groups. In addition, by subjecting the surface of the base layer to a surface treatment such as ultraviolet irradiation, the crosslinking reaction between the base layer 101 and the elastic layer 102 can be assisted, and the adhesive strength can be further strengthened. Examples of primers other than those mentioned above include X-33-156-20, X-33-173A / B, and X-33-183A / B (all trade names, manufactured by Shin-Etsu Chemical Co., Ltd.). In addition, examples of primers include DY39-90A / B, DY39-110A / B, DY39-125A / B, and DY39-200A / B (all trade names, manufactured by Toray Dow Corning Co., Ltd.).
[0019] (Inorganic particles) Next, the inorganic particles 103 attached onto the elastic layer 102 will be described. The inorganic particles may have a functional group capable of reacting with a hydroxyl group substituted or generated by a hydrophilization treatment on the surface (first surface) of the elastic layer opposite to the surface facing the base layer, which will be described later, and examples of the functional group include a hydroxyl group, an amino group, etc. Examples of such particles include silica particles.
[0020] Hereinafter, an example in which silica particles are used as inorganic particles will be described. On the first surface of the elastic layer, at least a part of each of the silica particles is held so as to be exposed from the elastic layer, and the elastic layer and the silica particles are in direct contact with each other. In order to obtain a layer of silica particles that is almost one layer, it is preferable that the silica particles have low coagulation properties and a certain degree of uniformity in particle size. Specifically, silica particles with a particle size of 300 nm or more are preferable. In addition, from the viewpoint of uniformity during application, it is preferable that the silica particles have a particle size of 2 μm or less. The method for producing silica particles may be either a dry method or a wet method, but the dry method is preferred because it does not require a drying step in the production process. Examples of silica particles include Hypressica (trade name, manufactured by Ube Exsymo Co., Ltd.) and SeaHostar (registered trademark) KE (trade name, manufactured by Nippon Shokubai Co., Ltd.).
[0021] In the present disclosure, it has been found that it is possible to achieve both the toner releasability of an electrophotographic belt and the adhesiveness of an elastic layer to inorganic particles by defining the residual ratio of inorganic particles before and after a Taber abrasion test as an index of the adhesive force or retention force of inorganic particles such as silica particles to an elastic layer. Specifically, a Taber abrasion test was performed under conditions of a load of 4.90N, a rotation speed of 60 rpm, and a rotation number of 1000 using an abrasion wheel CS10F based on ASTM D1044. At this time, the ratio of the number of inorganic particles in the contact part of the abrasion wheel after the Taber abrasion test to the number of inorganic particles present in the part corresponding to the part before the Taber abrasion test is 70% or more. In addition, it is preferably 83% or more. An electrophotographic belt having silica particles firmly fixed onto the elastic layer in this manner is less likely to experience changes in toner release properties over time, even when used as an intermediate transfer belt for forming electrophotographic images over a long period of time, and makes it possible to stably form high-quality electrophotographic images.
[0022] (Method of fixing inorganic particles) A manufacturing method (method of fixing inorganic particles) for an electrophotographic belt in which inorganic particles held on the first surface of an elastic layer on a base layer do not fall off even in the above-mentioned Taber abrasion test will be described with reference to FIG. 3. That is, the method for producing the electrophotographic belt according to the present disclosure by fixing silica particles to the first surface of the elastic layer includes the following steps (i) to (iii). Step (i): Surface treatment step of the elastic layer; Step (ii): Coating of silica particles; Step (iii): Adhesion step of silica particles.
[0023] Silica is used as the inorganic particles and silicone rubber is used as the elastic body, and the silicone rubber of the elastic layer is surface-treated to replace the methyl groups with hydroxyl groups. Then, siloxane bonds are formed by a dehydration condensation reaction with the hydroxyl groups, which are the surface functional groups of the coated silica particles. Each step is described in detail below.
[0024] (Step (i): Surface treatment step of elastic layer) This step includes a step of subjecting the first surface of the elastic layer to a hydrophilic treatment. Specifically, the first surface is subjected to at least one treatment selected from the group consisting of plasma treatment, corona treatment, flame treatment, and UV treatment. A typical example of the treatment is corona discharge treatment (also simply called discharge treatment). As shown in Fig. 3(a), a corona discharge treatment is performed on the first surface 301 of the elastic layer 102. This causes the organic groups of the silicone rubber to be substituted with hydroxyl groups, as shown in Fig. 3(b). Specifically, when the silicone rubber is dimethyl silicone rubber, at least a portion of the methyl groups bonded to silicon atoms are substituted with hydroxyl groups.
[0025] (Step (ii): Coating step of silica particles) Silica particles 303 are applied onto the first surface 301 treated in step (i) to adhere the silica particles 303 onto the first surface 301 (FIG. 3(c)). The application method is not particularly limited, and examples thereof include dry application. Excess silica particles adhering to the surface of the elastic layer are removed with an air gun. Since the first surface of the elastic layer usually has tackiness, a single layer of silica particles can be formed on the first surface.
[0026] (Step (iii): Silica Particle Fixation Step) A dehydration condensation reaction is caused between the silica particles 303 and the hydroxyl groups bonded to silicon atoms of the silicone rubber in the elastic layer 102, thereby forming siloxane bonds between the silicone rubber and the silica particles (Figure 3(d)). The dehydration condensation reaction can be caused at room temperature (25°C), for example, but the reaction may be accelerated by heating. The temperature at which the film is heated is not particularly limited as long as the dehydration condensation reaction proceeds, but is preferably 100°C or higher to further accelerate the dehydration. In addition, the silica particles can be pressed against the first surface to embed the silica particles in the elastic layer to a certain extent, thereby increasing the contact area between the first surface and the silica particles, thereby further increasing the adhesion. The pressurizing means is not particularly limited as long as it can apply a uniform pressure over the entire tubular film under the heating temperature conditions. A specific pressurizing method is, for example, a method of pressing the silica particles against the first surface by utilizing the difference in thermal expansion coefficient between the inner mold and the outer mold, as disclosed in Patent Document 4. The pressure is not particularly limited as long as the degree of embedding of the silica particles in the elastic layer or the adhesion of the silica particles to the elastic layer after adhesion satisfies the above-mentioned requirements. 2 (1.47N / cm 2 ) or more, more preferably 0.30kgf / cm 2 (2.94N / cm 2The upper limit of the pressure is not particularly limited as long as the silica particles are not completely buried in the elastic layer. For example, the upper limit of the pressure is 3.00 kgf / cm. 2 (29.42N / cm 2 ) or less.
[0027] By going through the above steps (i) to (iii), the silica particles can be fixed onto the elastic layer in a nearly close-packed state and in the form of a single layer. If the surface treatment of the first surface in the above step (i) is not performed, siloxane bonds are not formed between the silicone rubber in the elastic layer and the silica particles. Therefore, even if the silica particles are fixed to the first surface by the tackiness of the elastic layer surface, the silica particles will be detached when used to form an electrophotographic image. Therefore, corona treatment is used in this embodiment. If the elastic layer is not treated, hydroxyl groups are not generated in the silicone rubber of the elastic layer, and siloxane bonds are not formed by dehydration condensation reaction with the hydroxyl groups on the silica particle surface, resulting in detachment of the silica particles. On the other hand, if the number of treatments is increased (the treatment time is extended), the particles will come off together with the rubber. This is believed to be due to the polymer of the silicone rubber being broken, resulting in a loss of strength. Therefore, the surface treatment of silicone rubber needs to be appropriately set according to the treatment equipment, conditions, and material type.
[0028] As one of the methods for fixing silica particles to the first surface of the elastic layer, for example, a method using a silane coupling agent is considered. However, according to the study by the present inventors, the silica particles fixed on the elastic layer using a silane coupling agent do not have the wear resistance according to the present disclosure. In the electrophotographic belt according to the present disclosure, the silica particles are directly siloxane-bonded to the silicone rubber in the elastic layer, so that sufficient adhesion strength can be obtained even if the amount of silica particles embedded in the elastic layer is small. Therefore, the flexibility of the first surface of the surface layer due to the inorganic particles being embedded in the vicinity of the first surface of the elastic layer is not easily impaired, and further, the original function of the elastic layer (ability to follow the unevenness of paper) is not easily impaired. In addition, even when the elastic layer is repeatedly bent, the small amount of embedded silica particles makes it difficult for the elastic layer to be affected by interface stress due to displacement of the elastic layer, and it is possible to suppress the detachment of silica particles during continuous use.
[0029] (Electrophotographic image forming apparatus) An example of an electrophotographic image forming apparatus using the electrophotographic belt of the present disclosure will be described with reference to FIG. 2. Note that the present disclosure is not limited to the following description. The electrophotographic image forming apparatus 100 in FIG. 2 is a color electrophotographic image forming apparatus (color laser printer). In this electrophotographic image forming apparatus, image forming units Py, Pm, Pc, and Pk of the colors yellow (Y), magenta (M), cyan (C), and black (K) are arranged in the moving direction along the flat portion of the electrophotographic belt 7, which is an intermediate transfer body. Here, 1Y, 1M, 1C, and 1K respectively indicate electrophotographic photosensitive bodies, and 2Y, 2M, 2C, and 2K respectively indicate charging rollers. In addition, 3Y, 3M, 3C, and 3K respectively indicate laser exposure devices, 4Y, 4M, 4C, and 4K respectively indicate developing devices, and 5Y, 5M, 5C, and 5K respectively indicate primary transfer rollers. Since the basic configurations of the image forming units are the same, only the yellow image forming unit Py will be described in detail as to the image forming units. The yellow image forming unit Py has a drum-shaped electrophotographic photosensitive member 1Y (hereinafter also referred to as a "photosensitive drum" or a "first image bearing member") as an image bearing member. The photosensitive drum 1Y is formed by laminating a charge generating layer, a charge transport layer, and a surface protective layer in this order on an aluminum cylinder as a base. Further, the yellow image forming unit Py includes a charging roller 2Y as a charging means. By applying a charging bias to the charging roller 2Y, the surface of the photosensitive drum 1Y is uniformly charged.
[0030] A laser exposure device 3Y is disposed above the photosensitive drum 1Y as an image exposure means. The laser exposure device 3Y scans and exposes the uniformly charged surface of the photosensitive drum 1Y in accordance with image information, forming an electrostatic latent image of a yellow color component on the surface of the photosensitive drum 1Y. The electrostatic latent image formed on the photosensitive drum 1Y is developed by the developing device 4Y as a developing means with toner as a developer. That is, the developing device 4Y includes a developing roller 4Ya as a developer carrier, a regulating blade 4Yb as a developer amount regulating member, and contains yellow toner as a developer. The developing roller 4Ya to which the yellow toner is supplied is lightly pressed against the photosensitive drum 1Y in the developing section, and rotates in the forward direction with a speed difference from the photosensitive drum 1Y. The yellow toner conveyed to the developing section by the developing roller 4Ya adheres to the electrostatic latent image formed on the photosensitive drum 1Y by applying a developing bias to the developing roller 4Ya. As a result, a visible image (yellow toner image) is formed on the photosensitive drum 1Y.
[0031] The electrophotographic belt 7 is stretched around a drive roller 71, a tension roller 72, and a driven roller 73, and is moved (rotationally driven) in the direction of the arrow in the figure while in contact with the photosensitive drum 1Y. The yellow toner image formed on the photosensitive drum (first image carrier) that has reached the primary transfer portion Ty is primarily transferred onto the electrophotographic belt 7 by a primary transfer member (primary transfer roller 5Y) that is arranged opposite the photosensitive drum 1Y via the intermediate transfer belt 7.
[0032] Similarly, the above image forming operation is performed in each of the units Pm, Pc, and Pk of magenta (M), cyan (C), and black (K) as the electrophotographic belt 7 moves, and four-color toner images of yellow (Y), magenta (M), cyan (C), and black (K) are laminated on the electrophotographic belt 7. The four-color toner images are transported in accordance with the movement of the electrophotographic belt 7, and are transferred collectively at the secondary transfer portion T' by a secondary transfer member (secondary transfer roller 8) onto a recording material S (hereinafter also referred to as a "second image carrier") transported at a predetermined timing. In such secondary transfer, a transfer voltage of several kV is usually applied to ensure a sufficient transfer rate.
[0033] The recording material S is supplied to a conveying path from a cassette 12 in which the recording material S is stored by a pickup roller 13. The recording material S supplied to the conveying path is conveyed to a secondary transfer portion T' in synchronization with the four-color toner image transferred to the electrophotographic belt 7 by a conveying roller pair 14 and a registration roller pair 15. The toner image transferred to the recording material S is fixed by a fixing device 9 to become, for example, a full-color image. The fixing device 9 has a fixing roller 91 equipped with a heating means and a pressure roller 92, and fixes the unfixed toner image on the recording material S by applying heat and pressure. Thereafter, the recording material S is discharged outside the machine by a pair of conveying rollers 16, a pair of discharge rollers 17, etc. A cleaning unit for the electrophotographic belt 7 is disposed downstream of the secondary transfer portion T' in the driving direction of the electrophotographic belt 7, and removes residual toner remaining on the electrophotographic belt 7 without being transferred to the recording material S at the secondary transfer portion T'.
[0034] As described above, the process of electrically transferring a toner image from the photoconductor to the electrophotographic belt and from the electrophotographic belt to the recording material is repeated. Furthermore, by repeatedly recording on a large number of recording materials, the electrical transfer process is further repeated. EXAMPLES
[0035] The present disclosure will be specifically described below using examples, but the present disclosure is not limited to the following examples. [Example 1] (Formation of the base layer) Conductive carbon black (trade name: Denka Black, manufactured by Denki Kagaku Kogyo Co., Ltd.) was added to an N-methyl-2-pyrrolidone solution of polyamic acid (trade name: U Varnish A, manufactured by Ube Industries, Ltd.), which is a polyimide precursor. At this time, the conductive carbon black was added so that the amount of the conductive carbon black was 19% by mass relative to the total mass of the polyamic acid and the conductive carbon black, and mixed. The obtained mixture was applied to the outer peripheral surface of a cylindrical support made of stainless steel (SUS304) with an outer diameter of 330 mm and a length of 300 mm, the surface of which had been subjected to a blast treatment. Next, the cylindrical support was heated in a heating furnace at a temperature of 220°C for 30 minutes and at a temperature of 350°C for 30 minutes to polymerize the polyimide precursor applied to the outer peripheral surface of the cylindrical support, thereby forming a polyimide film. After cooling, the polyimide film was removed from the cylindrical support to obtain an endless belt-shaped base layer having a thickness of 70 μm. The outer peripheral surface of the base layer was irradiated with excimer UV to perform a hydrophilic treatment, after which a primer liquid (product name: DY39-051A / B, manufactured by Dow Toray) was applied thereto and the substrate was placed in a heating furnace and heated at 160°C for 10 minutes.
[0036] (Formation of elastic layer) 0.2 parts by mass of potassium-bis(trifluoromethanesulfonyl)imide (product name: EF-N112, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was mixed as an ion conductive agent with 100 parts by mass of addition curing liquid silicone rubber (product name: TSE3450 A / B, manufactured by Momentive Performance Materials, Inc.) Then, the mixture was stirred and degassed with a planetary stirring and degassing device (product name: HM-500, manufactured by Keyence Corporation) to prepare a coating liquid for the elastic layer. Next, the base layer prepared above was attached to a cylindrical core, and a ring nozzle for discharging rubber was attached coaxially with the core. The elastic layer coating liquid was supplied to the ring nozzle using a liquid pump and discharged from the slit to apply the elastic layer coating liquid onto the base layer. At this time, the relative movement speed and the liquid pump discharge amount were adjusted so that the silicone rubber layer after curing had a thickness of 280 μm, and a coating film was formed. The base layer was placed in a heating furnace while attached to the core, and heated at 130 ° C for 15 minutes and then at 180 ° C for 60 minutes to cure the coating film. After cooling, the base layer was removed from the core, and a base layer with an elastic layer laminated on the outer circumferential surface was obtained.
[0037] (Surface treatment process for elastic layer) The surface treatment of the elastic layer was performed using a corona discharge device (manufactured by Kasuga Denki Co., Ltd.). The treatment intensity in one scan was 27 kJ / m 2 The treatment was carried out once so that the above-mentioned conditions were satisfied.
[0038] (Silica particle coating process) Silica particles (product name: KE-S100, manufactured by Nippon Shokubai Co., Ltd., particle size: 1 μm) were evenly dry coated, and then the silica particles adhering in excess to the surface of the elastic layer were removed with an air gun.
[0039] (Silica particle adhesion process) The base layer on which the elastic layer coated with silica particles was laminated was fitted into an aluminum inner mold, and then covered with an outer mold made of stainless steel. In a heating furnace, the base layer was heated to 120°C at a heating rate of 50°C / min and held for 15 minutes, then cooled to room temperature and removed from the mold to obtain an electrophotographic belt. The diameter of the inner and outer molds was 0.5 kgf / cm at 120°C. 2 (4.9N / cm 2 ) pressure was developed.
[0040] As described above, an electrophotographic belt having silica particles adhered to an elastic layer was produced. This electrophotographic belt was used to carry out the following evaluations.
[0041] (Evaluation 1: Abrasion test) Based on ASTM D1044, the Taber abrasion test was carried out under the following conditions. Load: 4.90N Wear wheel: CS10F Rotation speed: 60 rpm Rotational speed: 1000
[0042] In the contact area between the abrasive wheel and the outer surface of the inorganic particle, the ratio of the number of the inorganic particles in the portion subjected to the Taber abrasion test after the Taber abrasion test to the number of the inorganic particles present in the contact area between the abrasive wheel and the outer surface of the inorganic particle before the Taber abrasion test was evaluated. At this time, 70% or more was considered acceptable. The evaluation was performed as follows. After the abrasion test, a scanning electron microscope (SEM, product name: S-4700, manufactured by Hitachi) was used to obtain an SEM image of the belt surface at a magnification of 20,000 times, and the image was binarized (particle part: white, particle detached part: black) using the image analysis software "ImageJ". The ratio of the number of pixels in the particle part: white to the number of pixels in the entire image was calculated and used as the survival rate.
[0043] (Rating 2: Image rating) The electrophotographic belt to be evaluated was installed as an intermediate transfer member in a full-color electrophotographic image forming apparatus (product name: imagePRESS C800, manufactured by Canon Inc.) In this case, the images were evaluated immediately after the start of printing and after 500,000 sheets were printed.
[0044] The image evaluation criteria are as follows. A: No degradation of image quality due to poor transfer is observed. B: There is a decrease in image quality due to poor transfer, but it is less than 5% of the printed area. C: Image quality has deteriorated due to poor transfer, but it is more than 5% and less than 10% of the printed area. D: Image quality is degraded by more than 10% due to poor transfer.
[0045] [Example 2 and Comparative Examples 1-2] In Example 2 and Comparative Examples 1 and 2, electrophotographic belts were produced in the same manner as in Example 1, except for the number of times the elastic layer was subjected to the corona surface treatment, as shown in Table 1 below.
[0046] [Comparative Example 3] Aminopropyltrimethoxysilane was applied to the surface of the elastic layer by spin coating. After that, it was heated at a temperature of 120°C for 2 hours, and then washed with ethanol to introduce amino groups to the surface of the elastic layer. Next, glutaraldehyde was applied (coating method, thickness) to the surface of the elastic layer to which the amino groups had been introduced, and the layer was left in an environment at a temperature of 25°C for 1 hour. Next, the surface treated with glutaraldehyde was washed with pure water and dried. Next, a colloidal dispersion of silica particles whose surface was modified with amino groups (product name PL-20, manufactured by Fuso Chemical Industry Co., Ltd., average primary particle diameter = 220 nm) was applied to the surface treated with glutaraldehyde. Thereafter, the silica particles were adhered and fixed to the surface of the elastic layer in the same manner as in Example 1 (adhering process of silica particles). In this way, an electrophotographic belt according to Comparative Example 3 was produced. Then, the obtained electrophotographic belt was evaluated in the same manner as in Example 1. Note that FIG. 4 shows the surface treatment process of the elastic layer in this comparative example.
[0047] [Table 1]
[0048] The evaluation results of the electrophotographic belts produced in Examples 1 and 2 and Comparative Examples 1 to 3 are shown in Table 1. In Example 1, good results were obtained in the abrasion test and the image evaluation after paper feed durability. In the abrasion test, slight detachment of silica was observed in Example 2. This is thought to be due to the fact that the rubber surface hardened due to the large number of corona treatments, and when external stress was applied, silica was detached due to cohesive failure in the hardened part of the rubber. In Comparative Example 1, since no corona treatment was performed, no bond was formed between the rubber surface and the silica, and the silica was easily detached when an external stress was applied. In Comparative Example 2, excessive rubber hardening occurred due to the corona treatment, and therefore detachment of silica was observed during the abrasion test and durability test. In Comparative Example 3, adhesion of silica particles to the surface of the elastic layer was confirmed at the initial stage. However, as a result of the abrasion test, the phenomenon of silica being detached together with a part of the elastic layer was confirmed, and the condition of the remaining ratio of silica particles according to the present disclosure was not met. The reason is unclear, but in the process of introducing amino groups or aldehyde groups into the elastic layer, the treating agent (aminopropyltriethoxysilane, glutaraldehyde) penetrated and reacted in a shallow region in the depth direction from the outer surface of the elastic layer. It is considered that the hardness of the silicone rubber present in that region increased and became embrittled. Therefore, it is considered that the silica particles were detached together with a part of the elastic layer during the abrasion test. [Industrial Applicability]
[0049] As described above, a siloxane bond is formed by a dehydration condensation reaction between the surface-treated elastic layer of the electrophotographic belt and the silica particles, and the elastic layer and the silica particles are adhered together, thereby achieving both toner releasability and suppression of silica particle detachment, providing an elastic ITB that is excellent for long-term use.
[0050] The present disclosure includes the following configurations. [Configuration 1] An electrophotographic belt comprising a base layer and an elastic layer on the base layer, the elastic layer includes rubber and has a thickness of at least 250 μm; a first surface of the elastic layer opposite to a surface facing the base layer holds a plurality of inorganic particles such that at least a portion of each of the inorganic particles is exposed from the elastic layer, and the elastic layer and the plurality of inorganic particles are in direct contact with each other; Regarding the outer surface of the electrophotographic belt, An electrophotographic belt characterized in that, when a Taber abrasion test is performed in accordance with ASTM D1044 using an abrasive wheel CS10F under conditions of a load of 4.90 N, a rotation speed of 60 rpm, and a rotation number of 1000, the ratio of the number of inorganic particles in a contact portion with the abrasive wheel after the Taber abrasion test to the number of inorganic particles present in a portion corresponding to the contact portion before the Taber abrasion test is 70% or more. [Configuration 2] 2. The electrophotographic belt of claim 1, wherein the inorganic particles are silica particles. [Configuration 3] 3. The electrophotographic belt of configuration 1 or 2, wherein the rubber is a silicone rubber. [Configuration 4] A method for producing an electrophotographic belt according to any one of configurations 1 to 3, comprising the following steps: (i) a surface treatment step of subjecting the first surface of the elastic layer to a hydrophilic treatment so as to include a hydroxyl group; (ii) a coating step of coating inorganic particles onto the first surface treated in step (i); (iii) a bonding step of bonding the elastic layer and the inorganic particles by a dehydration condensation reaction between the hydroxyl groups on the first surface and the surface functional groups of the inorganic particles. [Configuration 5] 5. The method for producing an electrophotographic belt according to claim 4, wherein the inorganic particles are silica particles. [Configuration 6] 6. The method for producing an electrophotographic belt according to configuration 4 or 5, wherein the first surface of the elastic layer is made of silicone rubber. [Configuration 7] an image forming unit including an image carrier, a charging means, an image exposure means, and a developing means; An electrophotographic image forming apparatus including an intermediate transfer body, a primary transfer member for primarily transferring a toner image formed on the image carrier onto the intermediate transfer body, and a secondary transfer member for secondarily transferring the toner image on the intermediate transfer body to a recording material, 4. An electrophotographic image forming apparatus, wherein the intermediate transfer member is the electrophotographic belt according to any one of configurations 1 to 3.
[0051] 1. Electrophotographic photoconductor (photoconductor drum) 2. Charge roller 3 Laser exposure device 4. Developing device 5 Primary transfer roller 7 Electrophotographic Belt 8 Secondary transfer outer roller 9 Fixing device 101 Base layer 102 Elastic layer 103 Silica particles
Claims
1. An electrophotographic belt comprising a base layer and an elastic layer on the base layer, the elastic layer includes rubber and has a thickness of at least 250 μm; a first surface of the elastic layer opposite to a surface facing the base layer holds a plurality of inorganic particles such that at least a portion of each of the inorganic particles is exposed from the elastic layer, and the elastic layer and the plurality of inorganic particles are in direct contact with each other; Regarding the outer surface of the electrophotographic belt, When a Taber abrasion test is performed according to ASTM D1044 using an abrasive wheel CS10F under conditions of a load of 4.90 N, a rotation speed of 60 rpm, and a number of revolutions of 1000, the ratio of the number of inorganic particles in the contact portion of the abrasive wheel after the Taber abrasion test to the number of inorganic particles present in the portion corresponding to the contact portion before the Taber abrasion test is 70% or more. Electrophotographic belt characterized in that:
2. 2. The electrophotographic belt of claim 1 wherein said inorganic particles are silica particles.
3. 2. An electrophotographic belt as defined in claim 1, wherein said rubber is a silicone rubber.
4. A method for producing an electrophotographic belt according to any one of claims 1 to 3, comprising the steps of: (i) a surface treatment step of subjecting the first surface of the elastic layer to a hydrophilic treatment so as to include a hydroxyl group; (ii) a coating step of coating inorganic particles onto the first surface treated in step (i); (iii) a bonding step of bonding the elastic layer and the inorganic particles by a dehydration condensation reaction between the hydroxyl groups on the first surface and the surface functional groups of the inorganic particles.
5. 5. The method for producing an electrophotographic belt according to claim 4, wherein said inorganic particles are silica particles.
6. The method of claim 4 , wherein said first surface of said elastic layer comprises silicone rubber.
7. an image forming unit including an image carrier, a charging means, an image exposure means, and a developing means; An electrophotographic image forming apparatus including an intermediate transfer body, a primary transfer member for primarily transferring a toner image formed on the image carrier onto the intermediate transfer body, and a secondary transfer member for secondarily transferring the toner image on the intermediate transfer body to a recording material, 4. An electrophotographic image forming apparatus, wherein the intermediate transfer member is the electrophotographic belt according to claim 1.
Citation Information
Patent Citations
Tubular film, production thereof and image forming apparatus using tubular film
JP1996187773A
Intermediate transfer body and image forming apparatus using the same
JP2014215470A
Intermediate transfer belt and image forming apparatus using the same
JP2015121585A
Member for electrophotography, method for manufacturing member for electrophotography, and electrophotographic image forming apparatus
JP2018194822A